Material design and performance of carbon monoxide‐fueled solid oxide fuel cells: A review - Wei Zhang; Yun Hang Hu (Energy Science & Engineering, 2023)
Abstract Solid oxide fuel cells (SOFCs) are electrochemical energy conversion devices with fuel flexibility. Since carbon monoxide (CO) is a major product of SOFC anodes operating with hydrocarbon fuels, direct utilization of CO as a fuel is expected for more efficient operation of SOFCs. A review on CO‐fueled SOFC technologies is imperative to promote research activities in this important field, but it has not been published. In this review, we summarize and comment on literatures in this field, with respect to (1) materials developed for three fundamental components (anode, cathode, and electrolyte), (2) power output and stabilization strategies, and (3) critical challenges and directions in the development of CO‐fueled SOFCs.